A fluorine-free flame-retardant PC recycled modified material and preparation method thereof
By using fluorine-free flame retardant composites in PC recycling materials, combined with silicon PC powder, phosphorus-containing flame retardant, nano-scale inorganic fillers and polydimethylsiloxane, the problem of PC recycling materials aging in high temperature and oil fume environments is solved, efficient flame retardant and physical performance improvement is achieved, and the durability and safety of home appliances are improved.
Patent Information
- Application Number
- CN202411248531.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-09-06
AI Technical Summary
Existing PC recycling materials are prone to aging in high temperatures and oil fume environments, resulting in reduced performance. Traditional fluorine-containing flame retardants have health risks, and large amounts of non-fluorine-based flame retardants affect physical performance.
Fluorine-free flame retardant composite is used, consisting of silicon PC powder, phosphorus-containing flame retardant, nano-scale inorganic filler and polydimethylsiloxane. The flame retardant and physical properties of the material are improved through compounding, and remain stable in high temperature and oil fume environments.
It achieves the maintenance of better flame retardant effects and physical properties in high temperature and oil fume environments, extends the service life of the material, and improves the durability and safety of home appliances.
Smart Images

Figure BDA0005031588730000061 
Figure BDA0005031588730000081 
Figure BDA0005031588730000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of polymer materials, and more specifically, to a fluorine-free flame-retardant PC recycled modified material and a preparation method thereof. Background Art
[0002] PC material is one of the five major engineering plastics. It has excellent transparency, impact resistance, temperature resistance, aging resistance and other characteristics. Therefore, it is widely used in electronics, automobile industry, construction industry, medical equipment, packaging materials, aerospace, sports equipment, optical products and other fields.
[0003] PC is made from petroleum. Currently, PC is recycled and reused to reduce energy loss. Flame retardants are usually added to PC recycled materials to produce flame-retardant PC recycled modified materials, which are used in household appliances such as the shells and other parts of range hoods, ovens, rice cookers, refrigerators, etc.
[0004] However, recycled PC comes from a variety of channels, including post-consumer recycling and industrial waste, which makes the composition and properties of recycled materials complex and variable, increasing the difficulty of recycling and reuse, resulting in lower performance of PC recycled products than PC products. In addition, long-term use in oil fume environments accelerates material aging, especially PC recycled materials used in smoke extractors; such as hotel range hoods, which produce a large amount of oil fume during use and are in a high temperature and heavy oil fume environment for a long time, causing PC recycled materials to age easily and reduce their performance.
[0005] Currently, the use of fluorinated flame retardants containing perfluoroalkyl or polyfluoroalkyl compounds can enable flame-retardant PC recycled materials to obtain better weather resistance and flame retardancy, while maintaining better physical properties. However, perfluoroalkyl or polyfluoroalkyl compounds pose health risks.
[0006] Non-fluorine flame retardants such as magnesium hydroxide and aluminum hydroxide are also used. Although they can achieve better flame retardant effects and improve the heat resistance of PC materials, a larger amount must be added to obtain a flame retardant effect similar to that of fluorinated flame retardants. A large amount added will also lead to a decrease in the physical properties of PC recycled materials. Therefore, further research is needed on the modification of fluorine-free flame retardant PC recycled materials. Summary of the invention
[0007] In order to obtain better flame retardant effect and reduce aging phenomenon caused by long-term exposure to high temperature and heavy oil fume environment, the present application provides a fluorine-free flame retardant PC recycled modified material and a preparation method thereof.
[0008] In the first aspect, the present application provides a fluorine-free flame retardant PC recycled modified material, which is composed of the following weight percentages: PC recycled material 60-87.2%
[0009] Fluorine-free flame retardant compound 12-21%
[0010] Antioxidant 0.3-0.8%
[0011] Toughener 0-20%;
[0012] The fluorine-free flame retardant composite is composed of silicon PC powder, phosphorus-containing flame retardant, nano-scale inorganic filler, and polydimethylsiloxane;
[0013] The nanometer-scale inorganic filler is magnesite powder and / or pumice powder; the phosphorus-containing flame retardant is tetraphenyl bisphenol A diphosphate and / or polydiphenyloxyphosphazene.
[0014] Silicon PC powder, namely silicon copolymer polycarbonate, is a high-performance engineering plastic obtained by copolymerizing siloxane groups introduced into polycarbonate. Compared with ordinary PC, it has better flexibility, hydrolysis resistance, high and low temperature resistance, flame retardancy and other properties; therefore, with phosphorus-containing flame retardants, nano-scale inorganic fillers, and polydimethylsiloxane, the fluorine-free flame retardant PC recycled modified material has better physical properties and flame retardancy, and has better flame retardant stability.
[0015] Tetraphenyl bisphenol A diphosphate has a large relative molecular weight, high thermal stability, low volatility, etc., and has good water decomposition resistance and high temperature resistance. Polydiphenyloxyphosphazene has good thermal stability and excellent flame retardant properties. It can inhibit the spread of flames and the combustion of materials, and improve the safety of materials. In addition, it also has good electronic properties and can be used in electronic devices, conductive materials and other fields. Therefore, the phosphorus-containing flame retardant using tetraphenyl bisphenol A diphosphate and / or polydiphenyloxyphosphazene can reduce migration or reduce the reduction of flame retardant effect in a high temperature and high humidity environment, so that the flame retardant PC recycled modified material obtains a better flame retardant effect.
[0016] Polydimethylsiloxane is an ultra-high molecular weight polydimethylsiloxane in the form of solid powder. As a flame retardant and processing aid, it is also used in thermoplastics to enhance toughness. Polydimethylsiloxane also has a low surface tension, which can reduce the interaction between silicon PC powder, phosphorus-containing flame retardant, and nano-scale inorganic filler particles, thereby improving the compatibility of silicon PC powder, phosphorus-containing flame retardant, and nano-scale inorganic filler in the flame retardant PC recycled modified material raw material system, thereby obtaining better flame retardant properties and impact toughness.
[0017] The main component of magnesite powder is magnesium carbonate. During the heating process, magnesite powder will release crystal water, structural water and carbon dioxide, thereby reducing the temperature of the flame on the surface of the material, reducing the concentration of combustible gas and oxygen, and forming a protective layer. In addition, magnesium oxide has the ability to catalyze thermal oxygen cross-linking reactions to form a carbonized film, further enhancing the flame retardant effect. Pumice powder is a porous volcanic rock, mainly composed of silicon dioxide, with a porous structure and high thermal properties. Pumice powder has an inhibitory effect on flame propagation, and can be combined with silicon PC powder, phosphorus-containing flame retardants, and polydimethylsiloxane to achieve a better flame retardant effect.
[0018] Furthermore, magnesite powder and / or pumice powder as nano-scale inorganic fillers, in addition to further improving the flame retardant effect, also play the role of toughening, oil and heat resistance, etc., combined with silicon PC powder, phosphorus-containing flame retardant, polydimethylsiloxane, it has better weather resistance, flame retardant properties and physical properties for PC recycled modified materials.
[0019] In summary, the present application uses silicon PC powder, phosphorus-containing flame retardant, nano-scale inorganic filler, and polydimethylsiloxane to compound and enhance the physical properties, flame retardant properties, and weather resistance of PC recycled modified materials. When used in household appliances such as range hoods, they can still maintain good flame retardant effects and physical properties in high temperature and oil smoke environments, thereby improving the durability and safety of household appliances.
[0020] The PC recycled modified material produced in this application is mainly used for the housing, filter screen, oil fume pipe, etc. of the smoke extractor. It can also be used for the refrigerator housing, the bottom legs of the oven, the bottom legs of the microwave oven, etc. It can be used in both oil fume and non-oil fume environments, and in the oil fume environment, it has better weather resistance, reduces aging, and improves durability and safety of use.
[0021] The total weight percentage of the PC recycled material, the fluorine-free flame retardant compound, the antioxidant and the toughening agent is 100%.
[0022] Furthermore, the weight percentage of the toughening agent of the present application is preferably 5%.
[0023] Preferably, the particle size of the nanoscale inorganic filler is 150-300 nm.
[0024] The above particle size range is the best choice for this application. Within this particle size range, it is easy to disperse and has a better toughening effect on PC recycled materials. In combination with silicon PC powder, phosphorus-containing flame retardant, and polydimethylsiloxane, the physical properties and flame retardant properties of fluorine-free flame retardant PC recycled modified materials are further improved.
[0025] Preferably, the weight ratio of the silicon PC powder, the phosphorus-containing flame retardant, the nano-scale inorganic filler and the polydimethylsiloxane is (10-15): (1-4): (3-5): 1.
[0026] When silicon PC powder, phosphorus-containing flame retardant, nano-scale inorganic filler and polydimethylsiloxane are compounded in a weight ratio of (10-15): (1-4): (3-5): 1, a better synergistic effect is achieved, so that the fluorine-free flame retardant PC recycled modified material obtains better physical properties, flame retardant properties and weather resistance. The weather resistance in this application refers to the ability to maintain better performance in a high-temperature oil fume environment, reduce aging and other phenomena, and improve the durability and safety of home appliances.
[0027] Preferably, the weight ratio of the magnesite powder to the pumice powder is (1-3): 1. When the magnesite powder and the pumice powder are compounded, a synergistic effect is achieved so that the fluorine-free flame-retardant PC recycled modified material obtains better physical properties, flame retardant properties and stable weather resistance.
[0028] Preferably, the fluorine-free flame retardant compound is a modified fluorine-free flame retardant compound, and the modified fluorine-free flame retardant compound is made from the following raw materials in weight percentage:
[0029] Isobornyl acrylate 1-3%
[0030] Initiator 0.02-0.04%
[0031] Nitrogen-containing silane 1.5-6.3%
[0032] Acrylate Phosphate 2-5%
[0033] Tris(2-hydroxyethyl)isocyanurate triacrylate 0.1-0.5%
[0034] 2,2-ethoxy-1-(trimethylsilyl)-1,2-nitrogen silanol 0.3-0.8%
[0035] The balance is fluorine-free flame retardant compound.
[0036] Isobornyl acrylate is used as an active diluent monomer, and nitrogen-containing silane contains nitrogen, which can improve the flame retardant effect, heat resistance, etc., and can improve the compatibility of inorganic fillers with silicon PC powder, phosphorus-containing flame retardants, and nano-scale inorganic fillers. At the same time, it can also further react with acrylate phosphate, tris (2-hydroxyethyl) isocyanuric acid triacrylate, and 2,2-ethoxy-1-(trimethylsilyl)-1,2-nitrogen silanol to form a macromolecular substance with a cross-linked network structure containing phosphorus, nitrogen, and silicon, which has better flame retardant and weather resistance. At the same time, it further promotes the dispersion compatibility of silicon PC powder, phosphorus-containing flame retardants, nano-scale inorganic fillers and PC recycled materials, so that the raw material system of PC recycled modified materials is evenly dispersed and tightly combined, thereby further improving the physical properties, flame retardant properties, and weather resistance of PC recycled modified materials.
[0037] Preferably, the nitrogen-containing silane is one or more of 3-(1,3-dimethylbutylene)aminopropyltriethoxysilane, N-[3-trimethoxymethylsilyl]propyl]-1,6-hexanediamine, and tetramethylguanidinopropyltrimethoxysilane.
[0038] 3-(1,3-dimethylbutylene)aminopropyltriethoxysilane, N-[3-trimethoxysilyl]propyl]-1,6-hexanediamine, and tetramethylguanidinylpropyltrimethoxysilane can all play a synergistic role, introduce nitrogen silicon, improve flame retardancy and heat resistance, and promote the compatibility of fluorine-free flame retardant PC recycled modified materials, making the raw material system tightly combined, reducing the possibility of migration and pyrolysis, and improving the weather resistance of PC recycled modified materials.
[0039] When 3-(1,3-dimethylbutylene)aminopropyl triethoxysilane, N-[3-trimethoxysilyl]propyl]-1,6-hexanediamine, and tetramethylguanidopropyl trimethoxysilane are compounded to play a synergistic role, and react with acrylate phosphate, tri(2-hydroxyethyl)isocyanuric acid triacrylate, and 2,2-ethoxy-1-(trimethylsilyl)-1,2-nitrosilanol, the macromolecular substance with a cross-linked network structure is blended and modified with silicon PC powder, phosphorus-containing flame retardant, nano-scale inorganic filler, and polydimethylsiloxane to obtain a modified fluorine-free flame retardant composite with better toughening, flame retardancy, and weather resistance. Further improve the physical properties, flame retardancy, and weather resistance of PC recycled modified materials. When the home appliances produced by it are used in high temperature and smoke oil environments, they can reduce aging phenomena and improve their durability and safety of use.
[0040] Preferably, the acrylate phosphate is alkyl acrylate phosphate and / or 2-hydroxyethyl methacrylate phosphate.
[0041] Alkyl acrylate phosphate and 2-hydroxyethyl methacrylate phosphate both contain phosphorus and acrylate groups. After further reaction with nitrogen-containing silane, 2-ethoxy-1-(trimethylsilyl)-1,2-nitrogen silanol, and tri(2-hydroxyethyl)isocyanuric acid triacrylate, a cross-linked network of macromolecular substances is obtained. After being blended and modified with fluorine-free flame retardant compounds, the flame retardancy, physical properties and weather resistance of PC recycled modified materials are further improved.
[0042] Preferably, the modified fluorine-free flame retardant composite is prepared by the following method:
[0043] Weigh isobornyl acrylate, initiator, nitrogen-containing silane, acrylate phosphate, and 2,2-ethoxy-1-(trimethylsilyl)-1,2-nitrogen silanol and heat to react, then add tris(2-hydroxyethyl)isocyanuric acid triacrylate and mix evenly, continue to react, then add fluorine-free flame retardant compound and mix evenly to obtain a modified fluorine-free flame retardant compound.
[0044] After nitrogen-containing silane, acrylate phosphate, and 2,2-ethoxy-1-(trimethylsilyl)-1,2-nitrogen silanol are reacted, tris(2-hydroxyethyl)isocyanuric acid triacrylate is added to continue the further cross-linking reaction of the materials, and then further blended and modified with the fluorine-free flame retardant composite to further obtain the physical properties, flame retardant properties and weather resistance of the modified fluorine-free flame retardant composite. In a second aspect, the present application provides a fluorine-free flame retardant PC recycled modified material as claimed in claim 1, which is prepared by the following method:
[0045] Weigh nano-scale inorganic filler and polydimethylsiloxane and mix them evenly to obtain a mixture A; weigh silicon PC powder and phosphorus-containing flame retardant and mix them, grind them to obtain a mixture B; mix the mixture A and the mixture B evenly to obtain a fluorine-free flame retardant composite;
[0046] According to the weight percentage, the PC recycled material, the fluorine-free flame retardant composite material and the antioxidant are weighed and mixed evenly, melt-extruded, cooled, dried and granulated to obtain the PC recycled modified material.
[0047] The above process is simple to operate and has high production efficiency. The mixture A and mixture B formed by mixing are then mixed, which is beneficial to improving the mixing uniformity of the fluorine-free flame retardant composite material. After the PC recycled material, fluorine-free flame retardant composite material and antioxidant are evenly mixed, melt extruded, cooled, dried, baked and granulated, the raw materials in the raw material system of the obtained PC recycled modified material are fully mixed and uniform, and have better physical properties, flame retardant properties and weather resistance. When it is used in the production of range hood accessories, it has better high temperature resistance, oil fume resistance, and better physical properties and flame retardant properties.
[0048] In summary, this application has the following beneficial effects:
[0049] 1. This application uses silicon PC powder, phosphorus-containing flame retardant, nano-scale inorganic filler, and polydimethylsiloxane to compound to enhance the physical properties, flame retardant properties, and weather resistance of PC recycled modified materials. When used in household appliances such as smoke extractors, they can still maintain better flame retardant effects and physical properties in high temperature and oil fume environments. Improve the durability and safety of household appliances.
[0050] 2. Through the reaction of nitrogen-containing silane, acrylate phosphate, tris(2-hydroxyethyl)isocyanuric acid triacrylate, and 2,2-ethoxy-1-(trimethylsilyl)-1,2-nitrogen silanol, a macromolecular substance with a cross-linked network structure containing phosphorus, nitrogen, and silicon is formed, which has better flame retardant and weather resistance. At the same time, it further promotes the dispersion compatibility of silicon PC powder, phosphorus-containing flame retardant, nano-scale inorganic filler and PC recycled materials, so that the raw material system of PC recycled modified materials is evenly dispersed and tightly combined, thereby further improving the physical properties, flame retardant properties and weather resistance of PC recycled modified materials. DETAILED DESCRIPTION
[0051] The present application is further described in detail below with reference to the embodiments.
[0052] Introduction of some raw materials:
[0053] Table 1 Introduction of some raw materials
[0054]
[0055] Example
[0056] Example 1
[0057] A preparation method of a fluorine-free flame-retardant PC recycled modified material is prepared by the following method:
[0058] Nano-scale inorganic filler and polydimethylsiloxane are weighed in weight ratio and mixed evenly to obtain mixture A; silicon PC powder and phosphorus-containing flame retardant are weighed and mixed, then put into a grinder for grinding, and sieved through 800 mesh to obtain mixture B; mixture A and mixture B are mixed evenly to obtain a fluorine-free flame retardant composite material.
[0059] Weigh 78.7 kg of PC recycled material, 21 kg of fluorine-free flame retardant composite material, and 0.3 kg of antioxidant, heat them until they are melted, stir them at a speed of 20 r / min for 30 min, and then transfer them to a twin-screw extruder for mixing, heat them until they are melted and extrude them. The screw speed is 400 rpm, and the set temperatures of the twin-screw extruder are 240°C, 250°C, 260°C, 270°C, 280°C, 265°C, and 255°C. After extrusion, they enter a cold water tank for cooling, and then enter an oven at 150°C for drying for 5 seconds, and then enter a granulator for granulation to obtain a flame retardant PC recycled modified material.
[0060] The fluorine-free flame retardant composite material is composed of PC powder, phosphorus-containing flame retardant, nano-scale inorganic filler and polydimethylsiloxane in a weight ratio of 15:1:3:1, wherein the nano-scale inorganic filler is magnesite powder, and the particle size of the nano-scale inorganic filler is 150-300nm. The phosphorus-containing flame retardant is tetraphenyl bisphenol A diphosphate; and the antioxidant is antioxidant 1010.
[0061] Example 2-3
[0062] The difference between Example 2-3 and Example 1 is that the amount of raw materials used is different, as shown in Table 2:
[0063] Table 2 Raw material dosage of Examples 1-3 (kg)
[0064] raw material Example 1 Example 2 Example 3 PC recycled material 78.7 80 87.2 Fluorine-free flame retardant compound 21 19.5 12 Antioxidants 0.3 0.5 0.8
[0065] Example 4
[0066] The difference between Example 4 and Example 2 is that the fluorine-free flame retardant composite material is composed of PC powder, phosphorus-containing flame retardant, nano-scale inorganic filler, and polydimethylsiloxane in a weight ratio of 10:4:5:1.
[0067] Example 5
[0068] The difference between Example 5 and Example 4 is that the phosphorus flame retardant is composed of tetraphenyl bisphenol A diphosphate and polydiphenyloxyphosphazene in a weight ratio of 1:1.
[0069] Example 6
[0070] The difference between Example 6 and Example 5 is that the nano-scale inorganic filler is composed of magnesite powder and pumice powder in a weight ratio of 3:1.
[0071] Example 7
[0072] The difference between Example 7 and Example 5 is that the nano-scale inorganic filler is composed of magnesite powder and pumice powder in a weight ratio of 1:1.
[0073] Example 8
[0074] The difference between Example 8 and Example 7 is that the fluorine-free flame retardant compound is a modified fluorine-free flame retardant compound, and the modified fluorine-free flame retardant compound is prepared by the following method.
[0075] In terms of weight percentage, 1% isobornyl acrylate, 0.04% initiator, 6.3% nitrogen-containing silane, 2% acrylate phosphate, and 0.3% 2,2-ethoxy-1-(trimethylsilyl)-1,2-nitrogen silanol were weighed and put into a reaction kettle and mixed evenly. The mixture was heated to 70° C. and reacted for 70 min. Then, 0.5% tris(2-hydroxyethyl)isocyanurate triacrylate was added and reacted for 1 h. Then, 89.86% fluorine-free flame retardant compound was added and mixed evenly to obtain a modified fluorine-free flame retardant compound.
[0076] The fluorine flame retardant composite material is composed of PC powder, phosphorus-containing flame retardant, nano-scale inorganic filler and polydimethylsiloxane in a weight ratio of 10:4:5:1; the nitrogen-containing silane is 3-(1,3-dimethylbutylene)aminopropyltriethoxysilane; the acrylate phosphate is 2-hydroxyethyl methacrylate phosphate; and the initiator is peroxy-3,5,5-trimethylhexanoic acid tert-butyl ester.
[0077] Examples 9-10
[0078] The difference between Example 9-10 and Example 8 is that the amount of raw materials used in the modified fluorine-free flame retardant composite is different, as shown in Table 3:
[0079] Table 3 Raw material dosage of Examples 8-10 (%)
[0080]
[0081] Embodiment 11
[0082] The difference between Example 11 and Example 9 is that the nitrogen-containing silane is 3-(1,3-dimethylbutylene)aminopropyltriethoxysilane, N-[3-trimethoxysilyl]propyl]-1,6-hexanediamine, and tetramethylguanidinylpropyltrimethoxysilane in a weight ratio of 2:2:1.
[0083] Example 12
[0084] The difference between Example 12 and Example 9 is that the acrylate phosphate is composed of alkyl acrylate phosphate and 2-hydroxyethyl methacrylate phosphate in a weight ratio of 1:1.
[0085] Example 13
[0086] The difference between Example 13 and Example 8 is that an equal amount of 2,2-ethoxy-1-(trimethylsilyl)-1,2-nitrogen silanol is replaced by acrylate phosphate.
[0087] Embodiment 14
[0088] The difference between Example 14 and Example 8 is that an equal amount of tris(2-hydroxyethyl)isocyanurate triacrylate is replaced by acrylate phosphate.
[0089] Embodiment 15
[0090] The difference between Example 15 and Example 8 is that the acrylate phosphate is replaced by nitrogen-containing silane in equal amounts.
[0091] Example 16
[0092] The difference between Example 16 and Example 12 is that: it also includes a toughening agent, and the toughening agent is MBS (South Korea LGEM505). The flame retardant PC recycled material includes PC recycled material, fluorine-free flame retardant composite material, tri(tridecyl) phosphite, and toughening agent 75kg, 19.5kg, 0.5kg, and 5kg.
[0093] Comparative Example
[0094] Comparative Example 1
[0095] The difference between Comparative Example 1 and Example 1 is that the nano-scale inorganic filler is replaced by silicon PC powder in equal amounts.
[0096] Comparative Example 2
[0097] The difference between Comparative Example 2 and Example 1 is that the fluorine-free flame retardant compound is aluminum hydroxide.
[0098] Performance testing
[0099] The fluorine-free flame-retardant PC recycled modified materials obtained in Examples 1-16 and Comparative Examples 1-2 were injection molded at a temperature of 275° C. to obtain several test samples, and then the corresponding test samples were used to test the flame retardancy and impact toughness. The specific data are shown in Table 4.
[0100] Detection method / test method
[0101] Flame retardant performance: refer to ASTMD2863 standard to test oxygen index;
[0102] Impact toughness: carried out in accordance with ASTM D256, the test conditions are 2mm V-notch, temperature is 25℃, and the thickness of the test sample is 3mm.
[0103] Weathering test: The test sample was placed in a weathering test device for 7 days. The test conditions were: temperature 150°C, and steam was continuously introduced. The steam was formed by mixing water vapor and oil vapor in a flow ratio of 1:1. The steam flow rate was 200L / h. The oil vapor was formed by mixing lard, peanut oil, and rapeseed oil in a weight ratio of 1:1:1 at high temperature.
[0104] The above experimental data are shown in Table 4;
[0105] Table 4 Experimental data of Examples 1-16 and Comparative Examples 1-2
[0106]
[0107]
[0108] Combining Example 1 and Comparative Examples 1-2 and Table 4, it can be seen that the oxygen index, impact toughness, oxygen index residual rate, and impact toughness of Example 1 are all higher than those of Comparative Examples 1-2, indicating that the compounding of the silicon PC powder, phosphorus-containing flame retardant, nanoscale inorganic filler, and polydimethylsiloxane of the present application has a better synergistic effect, and enables the fluorine-free flame retardant PC recycled modified material to obtain better flame retardant properties, physical properties, and weather resistance.
[0109] Combining Example 5 and Example 7 with Table 4, it can be seen that the oxygen index, impact toughness, oxygen index residual rate and impact toughness of Example 6 are all higher than those of Comparative Example 5. The specification uses dolomite powder and pumice powder to play a synergistic role, and cooperates with silicon PC powder, phosphorus-containing flame retardant and polydimethylsiloxane to play a better synergistic role, so that the PC recycled modified material obtains better physical properties, flame retardant properties and weather resistance.
[0110] Combining Example 7 and Example 8 and Table 4, it can be seen that the oxygen index, impact toughness, oxygen index residual rate and impact toughness of Example 8 are all higher than those of Example 7. The specification discloses that a macromolecular substance with a cross-linked network structure is formed by reacting nitrogen-containing silane, acrylate phosphate, tris(2-hydroxyethyl)isocyanurate triacrylate and 2,2-ethoxy-1-(trimethylsilyl)-1,2-nitrogen silanol, and is blended and modified with silicon PC powder, phosphorus-containing flame retardant and nano-scale inorganic filler to obtain a modified fluorine-free flame retardant composite and a raw material system of PC recycled modified material, thereby further improving the physical properties, flame retardant properties and weather resistance of PC recycled modified material.
[0111] Combining Example 8 and Example 13-15 and Table 4, it can be seen that the oxygen index, impact toughness, oxygen index residual rate and impact toughness of Example 13-15 are lower than those of Example 8, indicating that the present application adopts nitrogen-containing silane, acrylate phosphate, 2,2-ethoxy-1-(trimethylsilyl)-1,2-nitrogen silanol, tris(2-hydroxyethyl)isocyanuric acid triacrylate for compounding reaction, which has a better synergistic effect, and after blending and modifying with silicon PC powder, phosphorus-containing flame retardant, nanoscale inorganic filler and polydimethylsiloxane, the modified fluorine-free flame retardant composite is used in the raw material system of PC recycled modified material, so that the PC recycled modified material has better physical properties, flame retardant properties and weather resistance.
[0112] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A fluorine-free flame-retardant PC recycled modified material, characterized in that: Composed of the following percentages by weight: PC recycled materials 60-87.2% Fluorine-free flame retardant compound 12-21% Antioxidant 0.3-0.8% Toughening agent 0-20%; The fluorine-free flame retardant composite is composed of silicon PC powder, phosphorus-containing flame retardant, nano-scale inorganic filler and polydimethylsiloxane in a weight ratio of (10-15): (1-4): (3-5): 1; The nanometer-scale inorganic filler is magnesite powder and / or pumice powder; the phosphorus-containing flame retardant is tetraphenyl bisphenol A diphosphate and / or polydiphenyloxyphosphazene.
2. The fluorine-free flame-retardant PC recycled modified material according to claim 1, characterized in that: The particle size of the nano-scale inorganic filler is 150-300nm.
3. The fluorine-free flame-retardant PC recycled modified material according to claim 1, characterized in that: The weight ratio of the magnesite powder to the pumice powder is (1-3):
1.
4. The fluorine-free flame-retardant PC recycled modified material according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 1010, antioxidant 1076, antioxidant 264, antioxidant 2246, and antioxidant 168.
5. The fluorine-free flame-retardant PC recycled modified material according to claim 1, characterized in that: The fluorine-free flame retardant compound is a modified fluorine-free flame retardant compound, and the modified fluorine-free flame retardant compound is prepared from the following raw materials in weight percentage: Isobornyl acrylate 1-3% Initiator 0.02-0.04% Nitrogen-containing silane 1.5-6.3% Acrylate Phosphate 2-5% Tris(2-hydroxyethyl)isocyanurate triacrylate 0.1-0.5% 2,2-ethoxy-1-(trimethylsilyl)-1,2-nitrogen silanol 0.3-0.8% The balance is fluorine-free flame retardant compound.
6. The fluorine-free flame-retardant PC recycled modified material according to claim 5, characterized in that: The nitrogen-containing silane is one or more of 3-(1,3-dimethylbutylene)aminopropyltriethoxysilane, N-[3-trimethoxysilyl]propyl]-1,6-hexanediamine, and tetramethylguanidinopropyltrimethoxysilane.
7. The fluorine-free flame-retardant PC recycled modified material according to claim 5, characterized in that: The acrylate phosphate is alkyl acrylate phosphate and / or 2-hydroxyethyl methacrylate phosphate.
8. A fluorine-free flame-retardant PC recycled modified material according to any one of claims 5 to 7, characterized in that: The modified fluorine-free flame retardant composite is prepared by the following method: According to weight percentage, isobornyl acrylate, initiator, nitrogen-containing silane, acrylate phosphate, and 2,2-ethoxy-1-(trimethylsilyl)-1,2-nitrogen silanol are weighed and heated for reaction, and tris(2-hydroxyethyl)isocyanuric acid triacrylate is added and mixed evenly, and the reaction is continued, and the fluorine-free flame retardant composite is added and mixed evenly to obtain a modified fluorine-free flame retardant composite.
9. A method for preparing a fluorine-free flame-retardant PC recycled modified material according to any one of claims 1 to 8, characterized in that: Prepared by the following method: Weigh nano-scale inorganic filler and polydimethylsiloxane and mix them evenly to obtain a mixture A; weigh silicon PC powder and phosphorus-containing flame retardant and mix them, grind them to obtain a mixture B; mix the mixture A and the mixture B evenly to obtain a fluorine-free flame retardant composite; According to the weight percentage, the PC recycled material, the fluorine-free flame retardant composite material and the antioxidant are weighed and mixed evenly, melt-extruded, cooled, dried and granulated to obtain the PC recycled modified material.
Citation Information
Patent Citations
Interior train components having low smoke and low heat release, and methods of their manufacture
CN105849171A
Glass-fiber-reinforced flame-retardant polycarbonate composite material, and preparation method and applications thereof
CN110157174A